Identification of CTHRC1 as a novel candidate for neurodevelopmental disorders - Xu, Jie; He, Yuan; Li, Zhao; Zhou, Wenrong; Huang, Chunjian; Lu, Lu; Bajpai, Akhilesh K.; Li, Min (Frontiers in Aging Neuroscience, 2026)
BackgroundCognitive dysfunction affects over 50 million individuals worldwide, with Alzheimer’s disease (AD) representing two-thirds of cases. We identified CTHRC1 (Collagen Triple Helix Repeat Containing 1) as a novel candidate associated with cognitive function and neurodegeneration.MethodsHuman proteomic analysis revealed CTHRC1 as highly upregulated in AD patients (~5-fold increase, adj. p = 0.05), with corresponding elevation in 5xFAD mice. Single-cell RNA sequencing showed predominant astrocyte and oligodendrocyte progenitor expression. Using BXD mice, systems genetics analysis revealed associations between hippocampal CTHRC1 expression and 22 cognition-related phenotypes. PheWAS, ePheWAS, and GWAS analyses confirmed links to nervous system and AD-related traits.ResultseQTL mapping identified CTHRC1 as cis-regulated in hippocampus, and correlating with protein transport, transcription, and neurodegeneration pathways. Network analysis revealed 17 direct interactors, including key neurodegeneration genes (BACE1, NEFL, IRS1, VDAC1, SNCAIP) connecting CTHRC1 to core AD pathways (APP, MAPT, APOE, PSEN1/2). CTHRC1 overexpression in SH-SY5Y cells promoted tau degradation and modulated network partner expression.ConclusionCTHRC1 represents a central hub in cognitive function networks, suggesting therapeutic potential for neurodegenerative disorders.